2020
DOI: 10.37464/2020.371.3
|View full text |Cite
|
Sign up to set email alerts
|

A quality improvement pilot to initiate treatment summaries and survivorship care plans in oncology services in South Australia

Abstract: Aim: To review, test and refine standardised tools for nurses to initiate treatment summaries and care plans, and identify barriers and enablers to providing them.Background: This paper reports on a pilot study informed by the development of a Survivorship Framework in South Australia.Methods: Expression of interest was sought for adult medical oncology services to pilot standardised tools within existing services and resources. A quality improvement approach was used over three months with nurse practitioners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(17 citation statements)
references
References 27 publications
(33 reference statements)
0
17
0
Order By: Relevance
“…For instance, Meiklejohn et al. found that for Indigenous Australians, the use of plain language and culturally relevant information greatly facilitated their understanding and use of the information provided 23 . When such efforts were not taken, Indigenous Australian cancer survivors had difficulty relaying information to their family and healthcare workers, limiting their access to support within their community 23 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, Meiklejohn et al. found that for Indigenous Australians, the use of plain language and culturally relevant information greatly facilitated their understanding and use of the information provided 23 . When such efforts were not taken, Indigenous Australian cancer survivors had difficulty relaying information to their family and healthcare workers, limiting their access to support within their community 23 …”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies provided data to generate this theory regarding the importance of considering the social, cultural, and linguistic backgrounds of the cancer survivors 21–34 . For instance, Meiklejohn et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations